Relação do perfil da manometria anorretal como índice de massa corporal e sexo - Pasquatto, Tassiany da Silva (2023)
The body mass index (IMC) of overweight and obesity predisposes the development of pelvic floor (PF) disorders. There are studies that relate overweight and obesity with urinary incontinence and pelvic organs prolapses, but the effects in anorectal function are little described. One of the tools to evaluate the anorectal function is the anorectal manometry (ARM), but few studies used ARM to identify anorectal alterations associated with overweight and obesity. Therefore, the purpose of the present study is to verify the relation between ARM profile and differents BMI rates in patients with complaints of anorectal disorders to verify what is the impact of overweight and obesity when it comes to fecal incontinence. Retrospective study of secondary data analysis, developed at a private service of Gastroenterology and Pelvic floor Physiotherapy, in Cascavel – PR. The sample was constituted by 1791 patients of both sexes, aged between 18 and 45 years old, BMI equal or greater than 18 kg/m², that showed diagnostic or complaint about anorectal disorders and performed ARM at Gastroclínica’s service on the period between 2015 and 2019. It was analysed variables like sex, age, skin color, schooling, profession, anorectal complaints, weight, height, BMI and data from ARM. In the results we can notice a significantly higher number of female patients and patients with normal weight. Analyzing the relation between ARM profile and sex, it was observed that women showed significantly higher frequency of “decreased resting pressure” and statistically higher frequency of “decreased and normal contraction pressure”, while men have a frequency of “increased contraction pressure”. Besides, women have a significantly higher frequency of “bad sustained contraction pressure”. According to the BMI rates, we can notice a significant frequency of “increased rectal sensitivity” in underweight men; “increased resting pressure” and “dyssynergy” in women with normal weight; “increased resting pressure” and “dyssynergy” in overweight women; “increased resting pressure” in men with grade I obesity; “increased rectal sensitivity” in women with grade II obesity and between patients that belong to grade III obesity of BMI classification we observed a higher frequency of men with “increased resting pressure” and “good sustained contraction pressure”. The observed alterations did not correlate with the BMI rate. Considering the present study, it can be concluded that the alterations found in ARM in patients with complaints of anorectal disorders do not have relation with BMI in different sexes. Thus, overweight and obesity are not factors that get anorectal disorders worse